THE ROLEENTOMOPHAGY IN MEETING THE FOOD REQUIREMENTS OF THE RISING POPULATION - et. al., Dr.Shivaprasad G (International Journal of Modern Agriculture, 2021)
This paper examines the inclusion of insects as well as their consumption as human food which is termed as Entomophagy. Insects are verybeneficialnot only considering an ecosystem point of vision, but also as providinga protein-rich nutrient for human consumption. Some of the species which can be consumed are the drugstore beetle, the silkworm, the termite and the hawkmoth. The various plants existing in the ecosystem such as sweet potato, rice, soybean and green vegetablesand their combination fails to provide a diet that is lacking some essential nutrients required by humans. On most of the occasions these essential nutrients are provided byfoods derived from animals;for instance,fish, eggs, poultry, meat, dairy products, etc. Nevertheless, the most convenient way to obtain these essential nutrients is to extract from insects which is easier to produce as compared to the others techniques.Further, insects can also satisfy other useful biological roles. At the end this paper suggests some resolutions to earthly problems such as delivering precarious amino acids required by the individuals who suffer from a scarcity of additional conventional proteins resulting from the animals..